1996
DOI: 10.1136/hrt.75.5.513
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary blood supply in bidirectional cavopulmonary anastomosis with pulsatile pulmonary blood flow: quantitative analysis using radionuclide angiocardiography.

Abstract: Conclusions-Radionuclide angiocardiography allows the quantitative analysis of pulmonary blood supply in BCPA with sources of pulsatile blood flow except in patients with cavo-caval collaterals or bilateral BCPA. Non-pulsatile flow from BCPA is mainly directed to the ipsilateral lung, whereas pulsatile flow to the contralateral lung. Total perfusion of the ipsilateral lung is less than the perfusion of the contralateral lung. (Heart 1996;75:513-517) Keywords: congenital heart defects; cavopulmonary anastomo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…After surgery, only two patients had an index below this level. Similarly, our own experience demonstrated that a pulmonary artery originally smaller than normal on the side of the shunt can improve in size following a bidirectional cavopulmonary anastomosis, 15 corresponding with the demonstration by Reich et al 21 of preferential blood flow into such pulmonary arteries. Furthermore, when we calculated the Nakata index involving both the left and right pulmonary arteries in a subgroup of 23 patients from our previous study who had low pulmonary blood flow prior to the operation, a 29% increase was encountered after a median follow-up of 14 months.…”
Section: Effect Of Pulmonary Blood Flow On Pulmonary Arterial Size Prsupporting
confidence: 64%
“…After surgery, only two patients had an index below this level. Similarly, our own experience demonstrated that a pulmonary artery originally smaller than normal on the side of the shunt can improve in size following a bidirectional cavopulmonary anastomosis, 15 corresponding with the demonstration by Reich et al 21 of preferential blood flow into such pulmonary arteries. Furthermore, when we calculated the Nakata index involving both the left and right pulmonary arteries in a subgroup of 23 patients from our previous study who had low pulmonary blood flow prior to the operation, a 29% increase was encountered after a median follow-up of 14 months.…”
Section: Effect Of Pulmonary Blood Flow On Pulmonary Arterial Size Prsupporting
confidence: 64%
“…The lack of complete protection in this group may be explained by the uneven distribution of various sources of pulmonary blood supply. The BCPA provides up to 88% of blood flow to the ipsilateral lung and this may dilute the protective effect of hepatic factor from the competitive source 21. The occurrence of PAVM predominantly in the right lung following the Glenn procedure supports this hypothesis 1.…”
Section: Discussionmentioning
confidence: 87%